The collateralizability premium - Hengjie Ai; Jun E. Li; Kai Li; Christian Schlag (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
A common prediction of macroeconomic models of credit market frictions is that the tightness of financial constraints is countercyclical. As a result, theory implies a negative collateralizability premium; that is, capital that can be used as collateral to relax financial constraints provides insurance against aggregate shocks and commands a lower risk compensation compared with non-collateralizable assets. We show that a longshort portfolio constructed using a novel measure of asset collateralizability generates an average excess return of around 8% per year. We develop a general equilibrium model with heterogeneous firms and financial constraints to quantitatively account for the collateralizability premium.
urn:nbn:de:hebis:30:3-514999
Keywords: E2; E3; G12; 330; Cross-Section of Returns; Financial Frictions; Collateral Constraint